1990
DOI: 10.2134/jeq1990.00472425001900020004x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Factors Controlling the Mobilization of Inorganic Constituents from Fossil Fuel Combustion Residues: I. Review of the Major Elements

Abstract: Large quantities of fossil fuel combustion (FFC) wastes, such fly ash, bottom ash, flue gas desulfurization (FGD) sludge, and oil ash are being disposed of on land. There is a need to accurately assess the mobilization of elements that results from the weathering of these wastes. To help meet this need, available data on physical, chemical, mineralogical, extract, and leachate characteristics have been compiled and reviewed, and a comprehensive approach to understanding how major elements are mobilized from fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(99 citation statements)
references
References 1 publication
3
92
0
4
Order By: Relevance
“…Previous studies [53] [54] investigating eastern bituminous, western sub-bituminous, low-sulfur bituminous, sub-bituminous, lignite, and subbituminous PRB fly ash reported that the most alkaline (pH = 11.05 to 12.57) ash suspension was from sub-bituminous PRB ash. Environmental weathering and leaching of Ca, Fe, and S may have contributed to the lower pH of the weathered ash, which is supported by previous findings that fly ash with a Fe/Ca ratio > 3 produces acidic suspensions, while ratios < 3 generate alkaline suspensions [55]. The fresh and weathered ash had Fe/Ca ratios of 0.21 and 0.20, respectively.…”
Section: Initial Ash Characteristicssupporting
confidence: 75%
“…Previous studies [53] [54] investigating eastern bituminous, western sub-bituminous, low-sulfur bituminous, sub-bituminous, lignite, and subbituminous PRB fly ash reported that the most alkaline (pH = 11.05 to 12.57) ash suspension was from sub-bituminous PRB ash. Environmental weathering and leaching of Ca, Fe, and S may have contributed to the lower pH of the weathered ash, which is supported by previous findings that fly ash with a Fe/Ca ratio > 3 produces acidic suspensions, while ratios < 3 generate alkaline suspensions [55]. The fresh and weathered ash had Fe/Ca ratios of 0.21 and 0.20, respectively.…”
Section: Initial Ash Characteristicssupporting
confidence: 75%
“…Class F fly ash is formed during the combustion of either bituminous or anthracitic type of coal (Mattigod et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…It is both a primary crystalline product during cement paste consolidation and a secondary phase which crystallizes in hardened concrete and it plays an important role in concrete deterioration in humid environments. In addition, ettringite, effectively absorbs in its structure poisonous oxoanions from alkaline solutions produced by drainage of mining and industrial by-products, and from leachate from cement-based waste matrices with serious implications in terms of environmental impact [4][5][6][7]. In this study we determine the complete elastic tensor of ettringite and we highlight the relationship between crystal structure and elastic anisotropy in comparison with Ca(OH) 2 .…”
Section: Introductionmentioning
confidence: 99%